Development of an approach and tool to improve the conceptual design process of the wing box structure of low-subsonic transport aircraft - Syamsudin, Hendri (Cranfield University, 2009)
To produce a better airframe design, it is imperative to investigate the problems of design and manufacturing integration early on at the conceptual design stage. A new design approach and support tool is required which will aid the designer in future product development. This is a particular necessity in the current context of increasing complexity and challenging economic situations. The present work focuses on the development of a design approach and design aids for designing metallic wingbox structures of low-subsonic transport aircraft with small wing sweepback angles. Its aims are two-fold: to assist in producing alternative structural concepts, and to capture the effects of new materials and manufacturing processes on weight and cost. It will form the basis for selecting the structural concept at the early stage of the design process. The target users of this design approach and tools are relatively inexperienced structural designers and students. The developed process and tools are quite general in their application as they use stand-alone modules which can be employed separately or jointly with existing techniques and tools used by industry, research centres and academia. A comparison of the result from the developed analytical tools against a detailed study undertaken by an aircraft company on the original configuration was made. It showed stress analysis and sizing results that were within a 10% margin. A case study was performed to investigate the reduction of Direct Operating Cost (DOC) of a turboprop transport aircraft by redesigning the wingbox structure. Weight reductions of wing box structure of 16% were achieved using new configurations and advanced metallic materials. The purchase price of the aircraft could also be reduced through use of cheaper labour and new manufacturing processes. These cost savings, if converted into DOC reductions, are only 0.36% of DOC due to fuel saving and 0.25% of DOC due to manufacturing cost reduction for the wingbox structure only. It is obvious that the overall DOC reduction is the result of the total impact of relative DOC effects due to fuel cost saving, material prices, labour rates, and manufacturing process improvements. Within the range of the calculated parameter values, the overall DOC reductions could be as much as 0.61% relative DOC. It appears that fuel prices, material cost and labour rates give greater impacts on DOC than high speed machining processes. Due to the use of advanced aluminium, maintenance cost is also predicted to be less. It has better fatigue life and fracture toughness than the standard aluminium and therefore will increase the aircraft maintenance periods for inspection and repair due to slower crack damage growth. This cost saving will contribute in reducing the life cycle cost of the aircraft. In addition, the number of crack stoppers could be reduced, therefore minimising weight and manufacturing cost. These benefits however have not been analysed.